IRONY AS REPRESENTATION OF RACIAL SEGREGATION IN AUGUST WILSON’S “FENCES” - Ihya Aditya Fahmi Maarif; Andang Saehu; Lili Awaludin (Saksama, 2022)
Irony is figurative language that is frequently employed in literary works as a way to add interest to the text. Irony is a figure of speech employed in a sentence so that the intended meaning is different from the real meaning of the word, according to various dictionaries. One of the historical occurrences in the United States was racial segregation, which was intended to be a diplomatic separation between white society and African American society but instead supplied the same level of discrimination. Considering how the history of discrimination is depicted in play through figurative language: irony, the researcher conducted a study that focused on August Wilson's play entitled Fences (1984). This study used the theory of irony from Perrine (1994), to analyze the types of irony found in Fences and several sources of journals and history books to describe the history of racial segregation in the United States of America that occurred. This study uses a descriptive qualitative method, and the main data is the script of the drama Fences. The research result showed the type of irony in this playscript are able represent the racial segregation in United States. In conclusion, Wilson as a playwright effectively used irony in almost every round of his drama and this irony was also able to describe the situation of racial segregation that had occurred in United States.